A preliminary investigation of anaerobically digested municipal sludge cake and contaminated soil for recycling by pyrolysis. (June 2020) - Sullivan, G.L.; Prigmore, R.M.; Knight, P.; Godfrey, A.R.
Abstract: This work has investigated the potential of pyrolysis as a recycling solution for two largely uncharacterised waste streams, anaerobically digested (AD) municipal sludge cake and brownfield soil (contaminated with oily sludge). Characterisation of emitted organic compounds from pyrolysis were captured in a solvent (acetone) scrubber and analysed by GC–MS. Both AD sludge cake and brownfield soil showed considerable promise for 'green-er' fuels, as a source of syngas (with CO supplementation) and volatile aromatics essential for fuel quality. However, these waste streams also generated significant amounts of additional highly toxic pollutants of varying chemistries, further emphasising the importance of using a trapping approach applicable to a broader range of chemicals. Pleasingly the acetone trap showed very good efficacy in capturing this breadth of chemistries, supporting its use as an alternative capture and preparative method, for monitoring volatile and semi-volatile organic tars. Graphical abstract: A diagrammatic representation of the laboratory-scale pyrolysis/gasification rig with scrubber and GC-TCD. Nitrogen gas can be exchanged for compressed air to change oxidative state of the environment. Unlabelled Image Highlights: Acetone solvent as a method of tar capture Acetone compatible with GCMS for tar identification Method validation shows good accuracy and precision for wide array of compounds. Anaerobically digested municipal sludge cake tars were identified from the acetone. Tars identified from brown field contaminated soil synonymous with oily waste.